CRITICAL METALLICITY FOR POPULATION II STARS - Vasiliev, E. O.; Shchekinov, Yu. A. (Одеські астрономічні публікації, 2008)
We present simple arguments about metallicity of transition from first stellar generation (population III) to the second one. We consider the efficiency of fragmentation in gas induced by thermal instability in cold gas layers and filaments (T < 104 K), and in the shells formed by supernovae explosions from first stars. We estimate the metallicity at which the gas behind shock waves becomes unstable against thermal instability. We argue that this metallicity is inherited by population II stars and can be thus treated as the critical metallicity.